Internal damping depending on the vibration amplitude measured on specimens AZ31 and AZ91 in as cast state and after homogenization annealing - Dresslerová, Zuzana; Palček, Peter (Univerzita Pardubice, 2014)
The article is focused on the analysis of the internal damping changes depending on the amplitude of the magnesium alloys AZ31 and AZ91 and their comparison. Internal damping reflects the ability of the material irreversibly dissipating mechanical energy of oscillations. That means, the material of high internal damping ability is able to significantly reduce the vibration amplitude. Dispersion of mechanical energy in the material is just one of the ways of energy transformation for example conversion of mechanical energy to heat energy. In experimental measurements only ultrasonic resonance method was used. This method is based on continuous excitation of oscillations of the test bar, and the entire apparatus vibrates at a frequency which is close to the resonance.